Ambra1 modulates the tumor immune microenvironment and response to PD-1 blockade in melanoma. Issue 3 (3rd March 2023) - Frias, Alex; Di Leo, Luca; Antoranz, Asier; Nazerai, Loulieta; Carretta, Marco; Bodemeyer, Valérie; Pagliuca, Chiara; Dahl, Christina; Claps, Giuseppina; Mandelli, Giulio Eugenio; Andhari, Madhavi Dipak; Pacheco, Maria Pires; et al.
Abstract : Background: Loss of Ambra1 (autophagy and beclin 1 regulator 1), a multifunctional scaffold protein, promotes the formation of nevi and contributes to several phases of melanoma development. The suppressive functions of Ambra1 in melanoma are mediated by negative regulation of cell proliferation and invasion; however, evidence suggests that loss of Ambra1 may also affect the melanoma microenvironment. Here, we investigate the possible impact of Ambra1 on antitumor immunity and response to immunotherapy. Methods: This study was performed using an Ambra1-depleted Braf V600E / Pten −/ − genetically engineered mouse (GEM) model of melanoma, as well as GEM-derived allografts of Braf V600E / Pten −/ − and Braf V600E / Pten −/ − / Cdkn2a −/ − tumors with Ambra1 knockdown. The effects of Ambra1 loss on the tumor immune microenvironment (TIME) were analyzed using NanoString technology, multiplex immunohistochemistry, and flow cytometry. Transcriptome and CIBERSORT digital cytometry analyses of murine melanoma samples and human melanoma patients (The Cancer Genome Atlas) were applied to determine the immune cell populations in null or low-expressing AMBRA1 melanoma. The contribution of Ambra1 on T-cell migration was evaluated using a cytokine array and flow cytometry. Tumor growth kinetics and overall survival analysis in Braf V600E / Pten −/ − / Cdkn2a −/ − mice with Ambra1 knockdown were evaluated prior to and after administration of a programmed cell death protein-1 (PD-1) inhibitor. Results: Loss of Ambra1 was associated with altered expression of a wide range of cytokines and chemokines as well as decreased infiltration of tumors by regulatory T cells, a subpopulation of T cells with potent immune-suppressive properties. These changes in TIME composition were associated with the autophagic function of Ambra1. In the Braf V600E / Pten −/ − / Cdkn2a −/ − model inherently resistant to immune checkpoint blockade, knockdown of Ambra1 led to accelerated tumor growth and reduced overall survival, but at the same time conferred sensitivity to anti-PD-1 treatment. Conclusions: This study shows that loss of Ambra1 affects the TIME and the antitumor immune response in melanoma, highlighting new functions of Ambra1 in the regulation of melanoma biology.